(3aQGFO GdeYGfi aj TQM MQR GdCeGfjs - (3CHh YHO Gddg eMeO Hf OGhO GdUgGLj GdeYQha HGHf BLQhes; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeHJOF HGdGMSGf GdoeJaVd HfYeI GdESdGe hGdEjeGf GdeaVd fhY GdEfSGf Ydi LejY SGFQ GdMjhGf s
(3BNQgG (B:s
(3hfbd QOkG Yf fGaY hcJGHjg hjDNP ef bhd GdfGXe CUM JbHdkG Cf gfGdc hLg BNQ Ohfg aj GdUMI hgh fbd GdMQcI aGYde Pdc hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3HMhGTjgG ebGHdGJ hJUMjMGJs
(3fSNI KGfjI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs